Route-to-Market Capability, Marketing Execution, and Organizational Performance in FMCG Distribution: The Moderating Role of Competitive Intensity - Hartono Tjong; Murpin Josua Sembiring; David Sukardi Kodrat (Politeknik Siber Cerdika Internasional, 2026)
Background: FMCG distributors in emerging markets must adapt their route-to-market (RTM) strategies to market changes; however, this adaptation often compromises operational consistency, which is crucial for maintaining sales performance and outlet loyalty. This creates a dilemma between flexibility and stability that has not yet been fully addressed within the distribution capability framework. Objective: This study investigates RTM capability as a higher-order organizational construct comprising five integrated first-order dimensions and examines how this capability drives organizational performance through marketing execution quality, conditioned by competitive intensity. Methods: This study employed PLS-SEM using data collected from 300 employees of Indonesian FMCG distribution companies. Results: The findings reveal that RTM capability significantly and positively influences marketing execution, which, in turn, significantly enhances organizational performance (p < 0.001). Marketing execution partially mediates the RTM–performance relationship (VAF = 42.2%), while competitive intensity moderates the RTM–execution relationship, amplifying execution returns under conditions of highly competitive rivalry. Conclusion: This study advances the Resource-Based View (RBV) and Dynamic Capabilities Theory by specifying the execution mechanism through which distributor-level capability generates organizational performance and by identifying competitive intensity as a boundary condition governing this mechanism.